Successful intravascular pulmonary lithotripsy in a child with chronic thromboembolic pulmonary hypertension. Issue 6 (13th March 2021) - Diepenbruck, Sabine; Dalla‐Pozza, Robert; Pattathu, Joseph; Haas, Nikolaus; Jakob, André
Abstract: Intravascular lithotripsy (IVL) is a novel method based on pulsatile ultrasonic pressure waves specifically aimed to modify circumferential and transmural calcium plaques. We report on the successful application of a shockwave IVL catheter® in a child with chronic thromboembolic pulmonary hypertension due to calcified thrombi in both lower lobes. Compared to conventional high‐pressure balloon angioplasty, a significant perfusion‐improvement was achieved with a shockwave IVL catheter® (4 mm) of the treated right pulmonary artery branch. Furthermore, subsequent surgical thrombectomy was reported to be considerably easier for the shockwave‐treated thrombotic areas than the high‐pressure balloon‐only‐treated thrombus. In conclusion, the shockwave IVL catheter® may be a promising option in chronic thromboembolic lesions in PA (pulmonary artery) position, and furthermore might be an option when treating children.